Socio-economic Dynamics of Social Insurance in Oman: A Model Approach - Ibrahim, Omer Ali; Devesh, Sonal (International Journal of Economics and Financial Issues, 2020)
The paper examines the socio-economic dynamics and challenges to the social insurance scheme in Oman, during the period 2002-2016, using secondary sources. The study adopts a confirmatory factor analysis (CFA), and develops a model to identify the determinants of social insurance coverage for active insured and elderly beneficiaries. The study finds evidence that social insurance coverage in Oman is low, amounting to 12.1 and 6.6% for the active insured and the elderly beneficiaries respectively. Results also show that the common economic factors that have an influence on social coverage for both groups include per capita GDP, the fixed capital formation and inflation, while globalization has an influence on the active insured only., Omanization is a common, non-economic factor for both groups, in addition to fertility rate for the active insured, and life expectancy for elderly beneficiaries. Economic factors were found to be more important than non-economic factors for social insurance coverage in Oman. Keywords: Social Insurance Determinants, Active Insured, Elderly Beneficiaries, Confirmatory Factor Analysis, Public Authority for Social Insurance, Oman JEL Classifications: C5, H55 DOI: https://doi.org/10.32479/ijefi.9058